43.1: Invited Paper: UB‐FFS: New Materials for Advanced Mobile Applications. Issue 1 (June 2015) - Engel, Martin; Bernatz, Georg; Götz, Achim; Hirschmann, Harald; Lee, Sang‐Kyu
Abstract : In the recent years, displays for mobile electronic devices have been revolutionized, mostly driven by smartphones and tablets. Strongest trends are (besides growing sizes) the ever‐increasing resolution, improved contrast, very good viewing angle and color performance. This went hand in hand with a trend to more "refined" display technologies, namely fringe field switching (FFS). Now, as the latest step, Ultra‐Brightness (UB‐) FFS is at the brink to widespread commercialization in mobile and IT displays. It can provide transmittance improvement of more than 15%. The Liquid Crystal (LC) plays a key role here, because UB‐FFS uses LCs with negative dielectric anisotropy — whereas "traditional" FFS uses LCs with positive dielectric anisotropy. There are two key challenges. First is providing LCs with a fast switching speed. Second point is keeping the high reliability level of FFS even though completely different materials with much higher challenges on reliability are used. In this paper the recent progress for both key points will be discussed.